The Relation between Telework and Social Capital in the Workplace—Evidence from Japan - Junki Niikura (International Telecommunications Society (ITS), 2024)
The purpose of this paper is to examine the impact of telework on social capital in the workplace in Japan. Telework1 has gained popularity due to the COVID-19 pandemic. According to a survey2 conducted by the research firm Persol, the teleworking rate was 25.6% as of July 13 to 18, 2022. Thus, roughly one in four workers in Japan is teleworking. In addition, the government is promoting the use of telework as a flexible work style. While telework is encouraged as a flexible way of working, the rate of telework implementation has not increased with the onset of the COVID-19 pandemic. One reason for this may be reflected in the results of a survey of attitudes toward telework, where both advantages and disadvantages were mentioned, with lack of communication cited as a top concern by both workers and management. According to a survey3 conducted by the Japanese Trade Union Confederation (JTUC) from June 5 to 9, 2020, 37.6% of teleworkers cited "lack of communication with superiors and colleagues" as a disadvantage4. In addition, according to the "Questionnaire on the Merits and Demerits Felt by Companies in Telework5" conducted by Teikoku Databank, Ltd., from February 4 to 8, 2022, 26.6% of companies cited "reduced internal communication and difficulty in communication" as a demerit of telework. The most frequently cited disadvantages of telework are those related to communication. Communication concerns in telework arise because the amount of information available is less than that available in person and because a method of communication must be adapted. Given that communication is the foundation of trust, this study questions whether such decreased information during the communication process fundamentally affects the social capital of coworkers in the workplace. In this paper, we hypothesize that a lack of communication undermines social capital in the workplace. To examine the above hypothesis, this study compares the social capital of teleworkers and nonteleworkers. Specifically, an internet survey ("Telework and Corporate Social Capital Survey") is conducted to ask teleworkers and nonteleworkers about their respective internal trust relationships. Based on the responses, a social capital variable is then created and compared to determine whether teleworkers' social capital is lower than that of nonteleworkers. The next section summarizes previous research on the relationship between telework and social capital.
Keywords: 330; Telework; Social Capital; Japan